Peran Tokoh Masyarakat Formal Dan Informal Pada Pengembangan Objek Wisata Tubing Bon Pondoh - Devina, Dea; Wahyono, Hadi (Teknik PWK (Perencanaan Wilayah Kota), 2024)
The development of tourism in Indonesia is currently focused on developing rural tourism due to the changing trend of conventional tourism destinations becoming traditional. Tubing Bon Pondoh is one of the tourist attractions based on local potential in the form of tubing curving activities that utilize irrigation canals and is located in Temanggung Regency. From its early development until now, formal and informal community figures have not directly participated in the development of the Tubing Bon Pondoh, especially formal community figures, the village head. The importance of the role of community figures, both formal and informal, is the aim of this article, which is to examine the role of formal and informal community figures in the development of the Tubing Bon Pondoh tourist attraction. Using qualitative methods with resource selection techniques using snowball sampling and thematic and qualitative descriptive analysis techniques, the information that can be presented in this article is regarding informal community figures who continue to carry out development activities for the Tubing Bon Pondoh tourist attraction even though there is no participation and support from the village head as formal community figures because it has the support of the district government, the tourism office, and the head of the Temanggung Regency Pokdarwis.